Quantitative Validation of Hematocrit Percentage Drop Cutoff Points in Postpartum Hemorrhage: An Automated Gravimetric Approach - Venance Basil Kway; José Enrique Calacuayo Rojas; Josué Sidonio Rodríguez Cuevas; Ursula Medina Moreno; José Sergio Camacho Juárez; Jorge Francisco Ayala González; Karla Krebs Larraga; Ilse Veronica Castro Martinez; Roberto Arturo Castillo Reyther; Antonio Gordillo Moscoso; Yang Pan (Maternal-Fetal Medicine)
Abstract. Objective:. To validate the hematocrit percentage drop cutoff points for blood loss in patients with postpartum hemorrhage (PPH) using the automated gravimetric method. Methods:. A prospective cohort study was conducted from January 2023 to July 2023, in which 107 patients 18 years of age and above were scheduled for elective cesarean with obstetrical indications. We excluded cases with difficulty quantifying blood loss, those with incomplete data, and those of patients who did not consent to participate. Blood loss was measured by an automated gravimetric system integrated into a suction blood collector and surgical gauze weighing systems to automatically sum up blood loss immediately after hysterectomy and fetal delivery. The percentage drop in hematocrit was determined by subtracting the 8-hour postsurgical from presurgical hematocrit, divided by presurgical hematocrit. We performed the Pearson correlation test, and the receiver operating characteristic curve was used to determine cutoff points, their sensitivity, and their specificity. The κ index was used to determine the diagnostic agreement between the two methods. Results:. A positive correlation was observed between the volume of blood loss and the percentage drop in hematocrit, with a Pearson correlation index of 0.70 and P < 0.0001. A 14% decrease in hematocrit had an 81.7% agreement rate, with a good κ index of 0.602, a sensitivity of 82.5%, and a specificity of 80.0%. A 10% drop in hemoglobin was sensitive (93.0%) but not very specific (56.0%) for blood loss greater than 1000 mL. Conclusion:. The automated gravimetric method strongly correlates with hematocrit changes, providing an accurate real-time diagnosis of PPH. Additionally, a hematocrit percentage drop can retrospectively indicate significant blood loss, aiding in managing patients at risk for long-term PPH complications.